2009
DOI: 10.1371/journal.pgen.1000694
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the INSIG2 Association with Obesity Including 74,345 Individuals: Does Heterogeneity of Estimates Relate to Study Design?

Abstract: The INSIG2 rs7566605 polymorphism was identified for obesity (BMI≥30 kg/m2) in one of the first genome-wide association studies, but replications were inconsistent. We collected statistics from 34 studies (n = 74,345), including general population (GP) studies, population-based studies with subjects selected for conditions related to a better health status (‘healthy population’, HP), and obesity studies (OB). We tested five hypotheses to explore potential sources of heterogeneity. The meta-analysis of 27 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
3
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 27 publications
1
55
3
4
Order By: Relevance
“…No heterogeneity in INSIG2 main effect estimates was found between studies with higher compared with lower mean subject age; however, contrasted studies overlapped considerably in age range, with mean ages lying between 41 and 58 years. 18 Nevertheless, this meta-analysis revealed an increased obesity risk for rs7566605 minor allele homozygotes in general population studies (odds ratio 1.092, P ¼ 0.035, 48 844 subjects from 16 studies), but a decreased obesity risk in population-based studies with subjects selected for better health status (odds ratio 0.796, P ¼ 0.028, 7640 subjects from 5 studies). Six other studies also indicated a tendency toward a protective effect of rs7566605 risk genotype CC on BMI or obesity status, 3,9,10,12,14 or on waist-to-hip ratio.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…No heterogeneity in INSIG2 main effect estimates was found between studies with higher compared with lower mean subject age; however, contrasted studies overlapped considerably in age range, with mean ages lying between 41 and 58 years. 18 Nevertheless, this meta-analysis revealed an increased obesity risk for rs7566605 minor allele homozygotes in general population studies (odds ratio 1.092, P ¼ 0.035, 48 844 subjects from 16 studies), but a decreased obesity risk in population-based studies with subjects selected for better health status (odds ratio 0.796, P ¼ 0.028, 7640 subjects from 5 studies). Six other studies also indicated a tendency toward a protective effect of rs7566605 risk genotype CC on BMI or obesity status, 3,9,10,12,14 or on waist-to-hip ratio.…”
Section: Introductionmentioning
confidence: 73%
“…3,[8][9][10][11][12][13][14][15][16][17] Combining all study results on INSIG2 suggest age as the most probable interaction candidate. A large metaanalysis 18 (34 studies, 74 345 individuals) confirmed association of INSIG2 with obesity across study designs when comparing extremes (eg, BMI Z32.5 kg/m 2 versus BMI o25 kg/m 2 ). No heterogeneity in INSIG2 main effect estimates was found between studies with higher compared with lower mean subject age; however, contrasted studies overlapped considerably in age range, with mean ages lying between 41 and 58 years.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, a meta-analysis involving a large sample size of more than 70 000 individuals has been carried out recently to examine the INSIG2 association with obesity, and it found no evidence to support the association of the landmark SNP (rs7566605) with obesity. 28 Similarly, the SNPs that were identified for PD were not replicated in a large scale international study. 29 The second study for PD was only in its first stage of analysis at that time and it did not find any significant result.…”
Section: Gwas After Hapmap-the Progress Over the Past 5 Years The Firmentioning
confidence: 98%
“…However, this association could be replicated in only 5 of 9 cohorts drawn from different populations [Lyon et al, 2007]. A recent meta-analysis of 27 studies on Caucasian adults suggested an association of the INSIG2 CC genotype with extreme obesity, but not with obesity in general [Heid et al, 2009]. …”
Section: Introductionmentioning
confidence: 99%